Feng shui - Rono, Chito S.; Star Cinema (Firm). (Quezon City Star Cinema, 2004)
Joy and her family have just moved into a new home, in a sparsely populated village. For them, it is a time for new beginnings-A new change and a new hope. But what fortune awaits them... and woe the tragedies to follow.
VCD
Story, screenplay & directed by Chito S. Rono, Roy Iglesia; producer Tess V. Fuentes; executive producers Charo Santos-Concio, Malou N. Santos; directed by Chito S. Rono
Kris Aquino, Jay Manalo, Lotlot De Leon
Keywords: Horror films; Feature films; Feature films